2018
DOI: 10.2217/fon-2018-0379
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Emptive Skin Treatments to Prevent Skin Toxicity Caused by Anti-EGFR Antibody: The Real-World Evidence in Japan

Abstract: Pre-emptive skin treatments seem to be related to reducing subsequent dermatologist visits by severe skin toxicity prevention and gained popularity in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Yamazaki et al extracted large-scale clinical data and reported that preemptive skin treatment is widely available when EGFR inhibitors are used in Japan [ 14 ]. As a result of preventing severe skin-toxicity, dermatological visits decreased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yamazaki et al extracted large-scale clinical data and reported that preemptive skin treatment is widely available when EGFR inhibitors are used in Japan [ 14 ]. As a result of preventing severe skin-toxicity, dermatological visits decreased.…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed that branded medicines were given to patients. The skin treatment prescription content was set based on previous reports [ 14 , 16 ]. Costs were calculated according to 2020 medical fees and drug tariff in Japan [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in Japan, colorectal cancer research has been conducted using claims data [ 19 21 ]; however, the accuracy of the algorithms used has not been reported. Outside Japan, some studies have validated algorithms to identify colorectal cancers [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%